Empowering rural adolescents: Service learning for the prevention of risky sexual behavior in Bakung Village, Ogan Ilir Regency - Yulasteriyani, Yulasteriyani; Syafe’i, Akhmad; Istiqoma, Istiqoma; Putri, Cynthia Azhara; Randi, Randi; Yusnaini, Yusnaini; Ningsih, Sabda (Community Empowerment, 2025)
Adolescence is a critical developmental stage characterized by significant physical, emotional, and psychological changes, making comprehensive knowledge about sexuality crucial to mitigate the risks of unintended pregnancies, sexually transmitted infections, and other high-risk sexual behaviors. This community engagement initiative (Pengabdian kepada Masyarakat/PkM) aimed to educate adolescents in Bakung Village, Ogan Ilir Regency, on the dangers and consequences of risky sexual behavior. The intervention was delivered through a series of village-based lectures and educational sessions. Pre- and post-test assessments revealed a substantial improvement in participants' knowledge, with scores increasing from an average of 60% in the pre-test to 96% in the post-test. These findings underscore the effectiveness of service learning in enhancing adolescent understanding and awareness, contributing to the prevention of risky sexual practices in rural settings.